2015
DOI: 10.1002/acn3.259
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam effect during early neonatal development correlates with neuronal Cl

Abstract: ObjectiveAlthough benzodiazepines and other GABAA receptors allosteric modulators are used to treat neonatal seizures, their efficacy may derive from actions on subcortical structures. Side effects of benzodiazepines in nonseizing human neonates include myoclonus, seizures, and abnormal movements. Excitatory actions of GABA may underlie both side effects and reduced anticonvulsant activity of benzodiazepines. Neocortical organotypic slice cultures were used to study: (1) spontaneous cortical epileptiform activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 94 publications
(155 reference statements)
2
18
0
Order By: Relevance
“…Systematic measurements of [Cl − ] i in hundreds of neurons [44,45] with genetically-encoded ratiometric fluorophores such as Clomeleon [46], that also do not perturb the intracellular milieu, has provided additional insight into the developmental regulation of [Cl − ] i . These studies have revealed that neuronal [Cl − ] i does not decrease in all neurons simultaneously during development.…”
Section: [Cl−]i During Development: a Tale Of Two Transportersmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic measurements of [Cl − ] i in hundreds of neurons [44,45] with genetically-encoded ratiometric fluorophores such as Clomeleon [46], that also do not perturb the intracellular milieu, has provided additional insight into the developmental regulation of [Cl − ] i . These studies have revealed that neuronal [Cl − ] i does not decrease in all neurons simultaneously during development.…”
Section: [Cl−]i During Development: a Tale Of Two Transportersmentioning
confidence: 99%
“…A change in mental status and seizures are among the most common presentations of HIE in neonates [171]. Importantly, the most common anti-convulsive medications used at this age (phenobarbital, phenytoin, and benzodiazepines) have poor effectiveness [37,172,173] which is correlated with high [Cl − ] i in the neocortex during early development [44,45]. This high [Cl − ] i can be further exacerbated by Cl − accumulation during ensuing seizure episodes [13,174].…”
Section: Edema Mri Diffusion Changes Seizures and Anticonvulsant Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of neuronal [Cl - ] i in the deeper regions in both thalamus and neocortex support the developmental decrease of [Cl - ] i . Further support of the notion of a developmental decrease in [Cl - ] i comes from the intact preparations of the spinal cord [ 29 , 30 ] and retina, where sectioning trauma is not an issue [ 31 ], and the neocortical organotypic culture slice model [ 32 ]. In the neocortical organotypic culture slice, there is a progressive decrease in [Cl - ] i with no depth correlation during different days in vitro [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuron cultures have already yielded great insights into homeostatic plasticity mechanisms, such as Long-Term Potentiation, LTP, Long-Term Depression, LTD (Karmarkar et al 2002;(Turrigiano et al 1998;Turrigiano 2008) , synaptic scaling, structural synaptic plasticity (Yasumatsu et al 2008;Tominaga et al 1994) , self-organization of neural networks (Johnson & Buonomano 2007) (Cruz-Martín & Schweizer 2008) , and the underlying mechanisms of brain disease (Glykys & Staley 2015) . Long term organotypic cultures provide a unique system where emergent properties of neural networks can be studied at the cellular and molecular level, with extremely precise experimental control.…”
Section: Introductionmentioning
confidence: 99%